HIV-1 infection and the lack of viral control are associated with greater expression of interleukin-21 receptor on CD8+ T cells. (1st July 2021) - Dalel, Jama; Ung, Seng K.; Hayes, Peter; Black, S. Lucas; Joseph, Sarah; King, Deborah F.; Makinde, Julia; Gilmour, Jill
Abstract : Objectives: Interleukin-21 (IL-21) has been linked with the generation of virus-specific memory CD8 + T cells following acute infection with HIV-1 and reduced exhaustion of CD8 + T cells. IL-21 has also been implicated in the promotion of CD8 + T-cell effector functions during viral infection. Little is known about the expression of interleukin-21 receptor (IL-21R) during HIV-1 infection or its role in HIV-1-specific CD8 + T-cell maintenance and subsequent viral control. Methods: We compared levels of IL-21R expression on total and memory subsets of CD8 + T cells from HIV-1-negative and HIV-1-positive donors. We also measured IL-21R on antigen-specific CD8 + T cells in volunteers who were positive for HIV-1 and had cytomegalovirus-responding T cells. Finally, we quantified plasma IL-21 in treatment-naive HIV-1-positive individuals and compared this with IL-21R expression. Results: IL-21R expression was significantly higher on CD8 + T cells ( P  = 0.0256), and on central memory ( P  = 0.0055) and effector memory ( P  = 0.0487) CD8 + T-cell subsets from HIV-1-positive individuals relative to HIV-1-negative individuals. For those infected with HIV-1, the levels of IL-21R expression on HIV-1-specific CD8 + T cells correlated significantly with visit viral load ( r  = 0.6667, P  = 0.0152, n  = 13) and inversely correlated with plasma IL-21 ( r  = −0.6273, P  = 0.0440, n  = 11). Lastly, CD8 + T cells from individuals with lower set point viral load who demonstrated better viral control had the lowest levels of IL-21R expression and highest levels of plasma IL-21. Conclusion: Our data demonstrates significant associations between IL-21R expression on peripheral CD8 + T cells and viral load, as well as disease trajectory. This suggests that the IL-21 receptor could be a novel marker of CD8 + T-cell dysfunction during HIV-1 infection. Abstract : Supplemental Digital Content is available in the text